Acquired quadriparesis in a child with unusual presentation - Anuar, Muhamad Azamin; Wan Nik Ahmad Mustafa, Wan Alina Khadijah; Abu Bakar, Asrar; Hasan, Taufiq Hidayat; Mohamed, Mossad Abdelhak Shaban (2019)
Introduction Acute onset quadriparesis can be a manifestation of a variety of neurological, metabolic or autoimmune conditions. Rarely, it could be one of many clinical presentations of juvenile dermatomyositis which belongs to the group of idiopathic inflammatory myopathies of childhood. We report the case of a 9-year old girl who presented with global myopathy over a two-month period.